Iceland's Economic and Financial Crisis: Causes, Consequences and Implications - Spruk, Rok (2010)
Iceland experienced a significant financial meltdown and subsequent economic downturn after the 2008/2009 financial crisis struck the country. It had been the worst crisis ever experienced by a small country from the late 20th century onwards. Since 1980s, Iceland's macroeconomic stability had been constantly deteriorated by the most volatile annual CPI and asset-price inflation dynamics in the OECD. More than a decade of robust growth dynamics left behind an internationally over-exposed banking sector which exceeded the size of country's GDP by nearly 10 times. The failure of Lehman Brothers and a global credit crunch, in turn, raised CDS rates on Icelandic banks which immediately declared insolvency after the global interbank lending froze. The paper provides a comprehensive analysis of the macroeconomic, banking and financial background of the crisis. It also provides a short-term analysis of Iceland's macroeconomic outlook. The main findings of the article conclude that the depth of financial crisis is attributed to the recent decade of unadjusted monetary policy which failed to prevent sharp appreciation of the krona and thus created sufficient conditions for significant asset-price inflation, high interest rate differential and the largest banking collapse in small and open economies. As the size of the banking sector was several times the country's GDP, Icelandic central bank failed to act as a lender of the last resort. The paper concludes that, to prevent future crises of similar proportions, it is impossible for a small country to have a large international banking sector, its own currency and an independent monetary policy.